Life cycle analysis of ammonia-driven calcium looping processes for post-combustion CO2 capture in NGCC power plants - Zheng, Yawen; He, Song; Liu, Jianhui; Wang, Junyao; Zhu, Mingming; Yang, Guang; Wang, Wenxiang (Elsevier, 2025)
Integrating calcium looping (CaL) based carbon capture and storage (CCS) technology with an existing natural gas combined cycle (NGCC) power plants offers a promising solution for low-carbon energy production. This work introduces a novel NH3-driven CaL process for retrofitting NGCC plants. The economic performance and environmental impacts of the process were analyzed through life cycle analysis and compared with those of conventional oxy-fuel CaL and solar-driven CaL technologies. Results indicate that, the NH3-driven CaL demonstrates with a very low energy penalty of only 2.6 points, while the solar-driven CaL method faces a 14-points energy penalty. From an environmental perspective, the NH3-driven CaL method, with considering various ammonia sources, significantly impacts the environment more than oxy-fuel and solar-driven methods, with global warming potential values of 207.7 (oxy-fuel), 170.7 (solar), and 197.6–258.8 g CO2-eq/kWh (green NH3). Economically, based on an annual operation time of 4000 h of NGCC, the solar-driven CaL system has the lowest Life Cycle Cost of GHG Removed (LCOR) at 247.7 $/t CO2. With anticipated reductions in ammonia prices to 240 $/t in 2050, the NH3-driven CaL system is expected to gain a significant advantage in economic at 46.5 $/t CO2 when natural gas price is 0.6 $/Nm3. And it is important to pay attention the clean production process of ammonia to reduce its impact on the environment.
Keywords: Environmental Sciences; Ammonia; Post-combustion CO2 capture; Calcium looping; Natural gas combined cycle; Life cycle analysis